Efficacy of a Modified Sepsis System on the Mortality Rate of Septic Shock Patients in the Emergency Department of Siriraj Hospital - Rakpraisuthepsiri, Natvadee; Surabenjawong, Usapan; Limsuwat, Chok; Lertvipapath, Ploylarp (Journal of Health Science and Medical Research, 2023)
Objective: To compare the 28-day mortality rate between pre- and post-implementation of a modified sepsis fast-track system. Material and Methods: A cross-sectional cohort study was conducted at the Emergency Room (ER) of Siriraj Hospital, Bangkok. All patients who were diagnosed with septic shock and who received antimicrobial treatment at admission in the ER were included. Results: In total, 420 patients were included in the study, split into 210 patients in the pre-protocol group and 210 patients in the post-protocol group. Comparing between pre- and post-modified sepsis fast-track system implementation, the patients who received antimicrobials within 1 hour numbered 140 (66.7%) and 175 (83.3%), respectively (OR 2.5, 95% CI 1.57–3.97, p-value<0.001). The 28-day mortality rates of the pre- and post-protocol groups were 44.8% vs. 34.8% (p-value=0.036). According to the multivariate analysis, the factors that were significantly related to 28-day mortality in patients with septic shock were age greater than 75 years, diabetes mellitus, and initial SOFA score >9. Conclusion: Implementation of a modified sepsis program improved the time to first antimicrobial administration and decreased the 28-day mortality for patients with septic shock in the ER.